Airway epithelial integrin β4‐deficiency exacerbates lipopolysaccharide‐induced acute lung injury. Issue 11 (21st May 2021) - Jiang, Wang; Wang, Jin‐Mei; Luo, Jin‐Hua; Chen, Yu; Pi, Jiao; Ma, Xiao‐Di; Liu, Cai‐Xia; Zhou, Yang; Qu, Xiang‐Ping; Liu, Chi; Liu, Hui‐Jun; Qin, Xiao‐Qun; et al.
Abstract: Airway epithelial cells, the first barrier of the respiratory tract, play an indispensable role in innate immunity. Integrin β4 (ITGB4) is a structural adhesion molecule that is involved in the pathological progression of acute inflammatory diseases and is downregulated in asthmatic patients. Research has shown that endothelial ITGB4 has proinflammatory properties in acute lung injury (ALI). However, the role of epithelial ITGB4 in a murine ALI model is still unknown. This study investigated the role of ITGB4 in lipopolysaccharide (LPS)‐induced ALI. We found that ITGB4 in the airway epithelium had remarkably increased after the introduction of LPS in vivo and in vitro. Then, we constructed airway epithelial cell‐specific ITGB4 knockout (ITGB4 −/− ) mice to study its role in ALI. At a time point of 12 h after the tracheal injection of LPS, ITGB4 −/− mice showed increased macrophages (mainly M1‐type macrophages) and neutrophil infiltration into the lungs; inflammation‐related proteins including interleukin (IL)‐6, tumor necrosis factor, and IL‐17A were significantly elevated compared to their levels in ITGB4 +/+ mice. Furthermore, we investigated the role of ITGB4 in the anti‐inflammatory response. Intriguingly, in the ITGB4 −/− + LPS group, we found significantly reduced expression of anti‐inflammatory factors, including IL‐10 messenger RNA (mRNA) and ARG‐1 mRNA. We also observed that monocyte chemotactic protein (MCP‐1) increased significantly both in vivo and in vitro. Airway epithelium activates macrophages, most likely driven by MCP‐1, which we confirmed in the coculture of epithelia and macrophages. These phenomena indicate that ITGB4 in airway epithelial cells plays an important role in the process of inflammation and activation of macrophages in ALI. Overall, these data demonstrated a novel link between airway epithelial ITGB4 and the inflammatory response in LPS‐induced ALI. Abstract : Integrin β4 (ITGB4) is a structural adhesion molecule that is involved in the pathological progression of acute inflammatory diseases. We constructed airway epithelial cell‐specific ITGB4 knockout (ITGB4 −/− ) mice to study its role in acute lung injury (ALI). Overall, these data demonstrated a novel link between airway epithelial ITGB4 and the inflammatory response in lipopolysaccharide‐induced ALI.